Laminasi Kayu Sengon Sebagai Salah Satu Solusi Ketersediaan Kayu Untuk Bahan Bangunan - Agus Priyanto (Universitas Sarjanawiyata Tamansiswa, 2019)
Abstracts. The supply of wood that is quite durable and of high quality has not been able to meet the needs of building construction at the present time, especially in the future. Sengon wood (Paraserianthes falcataria) is a fast-growing type of plant that has a large increase (volume of wood per hectare per year) which is around 28 - 48 m3 / ha / year. To fulfill various human objectives, the majority of Sengon wood can be collected from the age of 6 years. With the use of lamination technology, wood remnants can be utilized to be made into wooden blocks of various sizes and various shapes. Lamination can make the strength of Sengon wood higher than solid wood beams.The test is carried out by physical and mechanical tests as well as the Sengon wood laminated sliding block test. In testing physical and mechanical properties based on ISO 1975 regulations. Testing of physical properties of Sengon wood includes wood density test and moisture content test. Testing the mechanical properties of Sengon wood includes fiber parallel compressive strength test, fiber perpendicular compressive strength test, tensile strength test, shear strength test and flexural strength test. Testing of Sengon wood laminated sliding blocks to determine the strength of lamination has a variation of 30 MDGL, 40 MDGL and 50 MDGL slurry adhesives with 3 replications of each shear test.The average density of Sengon wood is 0.315 t / m3 and the average moisture content of Sengon wood is 13.539%. The average compressive strength of fibers is 26.85 MPa and the compressive strength of fibers is 9.62 MPa. The average tensile strength of Sengon wood is 61.48 MPa and the average shear strength of Sengon wood is 5.31 MPa. In testing the flexural strength of Sengon wood an average of 43.18 MPa. Testing of Sengon wood laminate sliding block for 30 / MDGL obtained an average of 0.05 kg / mm2. In the shear block 40 / MDGL obtained an average shear strength of 0.02 kg / mm2. For the 50 / MDGL laminate shear block an average shear strength of 0.08 kg / mm2 was obtained.